Euphorbiaceae cactaceaeque novae vel criticae colombianae.- i (1943)
The botanical investigations now so vigorously conducted in the Republic of Colombia bring forth a continuous stream of novelties or critical forms in the Euphorbiaceae and the Cactaceae, which it is the purpose of these and following notes to describe and to discuss as they become known. Monographic work on selected groups is a clear necessity, but it is to my regret that I must set it aside for a later date. The study of large groups must often take into account  material which proves impossible to secure at present on loan. The plant-world of Colombia is so vast and rich that tolerably correct guesses-such as can made on smaller floras-are not possible Without consulting the type-specimens needed. Little else beyond descriptions and passing notes can be given at present.